CONCEPTION OF STRATEGIC MANAGEMENT ON THE ENTERPRISES OF THE OIL AND GAS COMPLEX IN THE CONTEXT OF ENERGY SECURITY OF UKRAINE - Kushlyk , O.Yu. (The actual problems of regional economy development, 2016)
The question of using of the strategic management as management technology on enterprises of the oil and gas complex with the aim of providing energy security of Ukraine has been considered. Interconnection of strategic plans through the state, branch administration and enterprises of oil and gas complex has been investigated. It has been determined that the oil and gas complex must not only effectively use its potential, but also create conditions for forming new competitive advantages and therefore enterprises and organizations of the oil and gas complex must become the transmitters of that. Concept of strategic management on enterprises of the oil and gas complex in the context of energy security of Ukraine has been investigated. JEL: M 20